Penatalaksanaan Fisioterapi Pada PPOK Di BBKPM Surakarta - Hidayat, Faqih; , Isnaini Herawati, S.Fis, S.Pd, M.Sc (2015)
qualification disorders that include chronic bronchitis, asthma, bronchiectasis and emphysema. Chronic Obstructive Pulmonary Disease is a condition that is irreversible or partially reversible relating to dypsnea or dyspnoea on exertion and a decrease in the flow of the passage of air in the lungs. Objective: To determine the results of physiotherapy in the management of COPD with breathing exercise modalities. Results: An increase in the expansion of the thoracic cage during inspiration after the method of breathing exercise therapy as much as six times that in the axilla of T0 = 1 cm difference becomes T6 = 2 cm, the area intercostalis 4th of T0 = 2 cm difference becomes T6 = 3 cm, the area processus xyphoideus of T0 = 2 cm difference becomes T6 = 3 cm. Conclusion: Can disismpulkan are successful in helping to improve the mobilization of the thoracic cage.